Pengaruh Suhu dan Lama Pemanasan Jus Buah Semangka Merah (Citrullus vulgaris (Schard.) Fursa. Terhadap Kandungan Vitamin C - Rahmiati Rahmiati; Helen Anjelina Simanjuntak (Program Studi S1 Farmasi, STIKES Senior, Medan, 2021)
Red watermelon (Citrullus vulgaris (Schard.) Fursa. is a fruit that is very popular with the Indonesian people because of its sweet, crunchy taste and high water content, and is rich in vitamin C. The fruit is eaten fresh or made into juice. This study aims to know the vitamin C content in red watermelon juice with variations in temperature and heating time. The research method was experimental design using a thermoreactor to measure the vitamin C content at variations in temperature and heating time. The samples used came from the Berastagi Tanah Karo area. The results showed that heating the best watermelon juice at a temperature of 30°C and heating time can affect the decrease in concentration in watermelon juice with a good time to use 15 minutes and 30 minutes.